2020
DOI: 10.21203/rs.3.rs-45287/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ganoderma (Ganodermataceae, Basidiomycota) species from the Greater Mekong Subregion

Abstract: The cosmopolitan Ganoderma is an important pathogen on arboreal plant hosts. Ganoderma is particularly diverse in tropical and temperate regions. It has long been used as traditional medicine because of its beneficial medicinal properties and chemical constituents. In this study, Ganoderma collections were made in tropical regions of Laos, Myanmar, Thailand, Vietnam and temperate Yunnan Province, China. The specimens are described based on micro-macro characteristics and phylogenetic analysis of combined ITS, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The host specificity of Ganoderma species is highly variable, but many species show striking host generalism (e.g. G. adspersum, G. applanatum, G. curtisii, G. philippi, G. resinaceum, G. zonatum) (Luangharn et al 2020). Although numerous Ganoderma species have a wide host range, the study of Ganoderma species occurring on different trees has recently yielded several new species.…”
Section: Species Diversity Of Ganodermamentioning
confidence: 99%
See 1 more Smart Citation
“…The host specificity of Ganoderma species is highly variable, but many species show striking host generalism (e.g. G. adspersum, G. applanatum, G. curtisii, G. philippi, G. resinaceum, G. zonatum) (Luangharn et al 2020). Although numerous Ganoderma species have a wide host range, the study of Ganoderma species occurring on different trees has recently yielded several new species.…”
Section: Species Diversity Of Ganodermamentioning
confidence: 99%
“…The genus shows a much higher diversity in Asia. As an example, Luangharn et al (2020) reported 23 Ganoderma species only from the Greater Mekong Subregion, out of which three species were new to science. In recent years the genus has been intensively studied in Asia and several new species have been described especially from China (e.g., Cao et al 2012;Cao and Yuan 2013;Li et al 2015Xing et al 2018;Hapuarachchi et al 2018;Liu et al 2019;Ye et al 2019).…”
Section: New Species Publication Ratementioning
confidence: 99%
“…Among the Ganoderma species, G. multipileum was discovered on a stump of decaying wood for the rst time in Taiwan (D. M. Wang et al, 2009). Since then, G. multipileum has been described based on morphology and phylogeny in subtropical and tropical countries such as China (Cao et (Luangharn et al, 2021). In previous reports, Ganoderma multipileum was described as a white-rot fungus that mainly decays dead softwood such as Sterculia nobilis, Delonix regia (D. M. Wang et al, 2009), and Pinus merkusii (Luangharn et al, 2021), as well as hardwood plants such as Dalbergia sissoo and Vachellia nilotica (Umar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%